SOFC/Gas Turbine Hybrid System: A simplified framework for dynamic simulation. (15th March 2019) - Rossi, Iacopo; Traverso, Alberto; Tucker, David
Highlights: A simplified dynamic model of an SOFC/Gas Turbine System is presented. The goal is to compute performance degradation of SOFC during normal operations. The NETL 430 kW SOFC/Gas Turbine Emulator is the target plant for modelling. Model validation is pursued against real test data. The model is developed within a Microsoft Excel/Visual Basic environment. Abstract: This paper describes a simplified framework to create dynamic models of SOFC/Gas Turbine Hybrid Systems. After some physical considerations on global SOFC/GT structure, the work focuses on the modelling approach. It embodies some empirical parameters, which can be derived from operating data or detailed simulation analysis. The framework results in a hybrid model – partly physics-based, partly data-driven – which covers a large range of working conditions. The resulting simplicity and robustness of the approach allows the potential adoption in different on-field applications such as fast response models for operators, control system development and validation, model-based controllers, as well as for dynamic performance evaluations. This last application is shown at the end of the paper, where the response of the model is compared with a real Cyber-Physical SOFC/Gas Turbine Emulator installed at the National Energy Technology Laboratory (NETL), Morgantown (West Virginia, USA).